Sex differences in outcomes following isolated coronary artery bypass graft surgery in Australian patients: Analysis of the Australasian Society of Cardiac and Thoracic Surgeons cardiac surgery database - Saxena, A.; Dinh, D.; Smith, J.; Shardey, G.; Reid, Christopher; Newcomb, A. (2012)
Objectives: Women undergoing isolated coronary artery bypass graft (CABG) surgery have been previously shown to be at an independently increased risk for post-operative morbidity and mortality. The current study evaluates the impact of sex as an independent risk factor for early and late morbidity and mortality following isolated CABG surgery. Methods: Data obtained between June 2001 and December 2009 by the Australasian Society of Cardiac and Thoracic Surgeons Cardiac Surgery Database Program was retrospectively analysed. Demographic, operative data and post-operative complications were compared between male and female patients using chi-square and t-tests. Long-term survival analysis was performed using Kaplan-Meier survival curves and the log-rank test. Independent risk factors for short- and long-term mortality were identified using binary logistic and Cox regression, respectively. Results: CABG surgery was undertaken in 21 534 patients at 18 Australian institutions; 22.2% were female. Female patients were generally older (mean age, 68 vs. 65 years, P < 0.001) and presented more often with congestive heart failure (P < 0.001), hypertension (P < 0.001), diabetes mellitus (P < 0.001) and cerebrovascular disease (P < 0.001). Women demonstrated a greater 30-day mortality (2.2% vs. 1.5%, P < 0.001) on univariate analysis but not on multivariate analysis (P = 0.638). Similarly, women demonstrated a greater late mortality than men on univariate analysis (P = 0.006) but not on multivariate analysis (P = 0.093). Women had a decreased risk of early complications including new renal failure (P = 0.001) and deep sternal wound infection (P = 0.017) but were more likely to require red blood cell transfusion (P < 0.001). Conclusions: Female patients undergoing isolated CABG surgery have a greater 30-day mortality which may be accounted for by a poorer pre-operative risk factor profile. Further investigation is required into the reasons for differential outcome after CABG based on sex. © The Author 2012. Published by Oxford University Press on behalf of the European Association for Cardio-Thoracic Surgery. All rights reserved.